Performance in Hand Coordination Tasks And Concurrent Functional MRI Findings in 13-Year-Olds Born Very Preterm - Tilli, Joni (My University, 2023)
Fine motor and coordination problems are frequently reported among adolescents born preterm. We aimed to assess performance in hand coordination tasks and to compare concurrent brain activation between adolescents born very preterm and full-term at 13 years. 34 right-handed adolescents born very preterm (gestational age <32 weeks/birth weight ≤1500 grams) and 37 controls born full-term in 2003-2006 in Turku University Hospital, Finland, were recruited. At 13 years, finger opposition and diadochokinesis were assessed, and brain functional magnetic resonance imaging (fMRI) data was acquired while the adolescents performed unimanual, self-paced hand coordination tasks in response to visual cue. Adolescents born very preterm performed similar to controls in hand coordination tasks. The very preterm group evoked greater brain activation than the controls in the right precentral gyrus (p=0.01) and in the right postcentral gyrus (p=0.02) during left hand finger opposition, and in the right postcentral gyrus during left hand diadochokinesis (p=0.03). Within the very preterm group, lower gestational age was associated with reduced activation in the left superior parietal lobule during right hand diadochokinesis (p=0.02). Regarding left hand tasks, lower gestational age was associated with stronger activation in the right cerebellar lobule V (p=0.03) and left cerebellar lobule VI (p=0.03) during finger opposition, and stronger activation in the right superior parietal lobule (p=0.03) during diadochokinesis. Very preterm birth affected hand coordination-related brain activation. Most of the effects were found for non-dominant hand. Clinical performance during the hand coordination tasks was similar in adolescents born very preterm and controls.

Pikkukeskosilla CP-vamman ilmaantuvuus on laskenut viime vuosikymmeninä. Kuitenkin lievemmät hienomotoriikan ja koordinaation ongelmat vaikuttavat yleistyneen. Hienomotorisilla taidoilla tarkoitetaan pienillä lihaksilla aikaansaatuja tarkkuutta vaativia liikkeitä. Riittävät hienomotoriset taidot ovat mm. edellytys tavanomaiselle koulunkäynnille. Tämän työn tarkoituksena oli tutkia pikkukeskosina (syntymä ennen 32. raskausviikkoa ja/tai syntymäpaino on ≤ 1500 grammaa) syntyneiden ja täysaikaisena syntyneiden verrokkien hienomotorisia taitoja ja hienomotoristen tehtävien aikaisia toiminnallisia aivokuvantamislöydöksiä 13 vuoden iässä. Tutkimus on osa PIPARI-seurantatutkimusta (Pienipainoisten riskilasten käyttäytyminen ja toimintakyky imeväisiästä kouluikään). Tutkimukseen osallistui 34 oikeakätistä pikkukeskosena syntynyttä nuorta ja 37 oikeakätistä täysiaikaisena syntynyttä verrokkinuorta. Kaikki tutkittavat olivat syntyneet Turun yliopistollisessa keskussairaalassa vuosina 2003-2006. Hienomotorisia taitoja arvioitiin Touwenin neurologiseen tutkimukseen kuuluvien sormien opponoinnin ja diadokokineesin avulla. Suoritukset videoitiin ja arvioitiin kokeneen lastenneurologin kanssa. Hienomotoriset tehtävät suoritettiin vielä uudelleen magneettikuvauksen aikana ja aivojen aktivaatiota mitattiin funktionaalisella magneettikuvauksella (fMRI). Tutkimuksen perusteella pikkukeskosina syntyneet nuoret suoriutuvat hienomotorisista testeistä kliinisesti arvioituna verrokkien tavoin. Sen sijaan pikkukeskosilla todettiin täysaikaisia verrokkeja voimakkaampaa aktivaatiota eidominantin (vasemman) käden hienomotoristen tehtävien aikana tietyillä aivoalueilla. Löydös osoittaa, että fMRI-tutkimuksella voidaan havaita pitkäkestoisia neuraalisten mekanismien muutoksia hyvin ennenaikaisen syntymän jälkeen tilanteissa, joissa eroavaisuuksia täysaikaisena syntyneisiin ei kliinisin menetelmin ole todettavissa.
Keywords: Fine motor, fMRI, follow-up, prematurity, pikkukeskonen, neurologia, hienomotoriikka, fMRI